A metal–organic framework supported iridium catalyst for the gas phase hydrogenation of ethylene. Issue 97 (19th November 2020) - Perlata, Ricardo A.; Huxley, Michael T.; Shi, Zhaolin; Zhang, Yue-Biao; Sumby, Christopher J.; Doonan, Christian J.
Abstract : Gas phase hydrogenation of ethylene by a MOF supported Iridium catalyst highlights the role of support and counteranion effects. Abstract : The mutable structures of metal–organic frameworks (MOFs) allow their use as novel supports for transition metal catalysts. Herein we prepare an iridium bis(ethylene) catalyst bound to the neutral N-donors of a MOF structure and show that the compound is a stable gas phase ethylene hydrogenation catalyst. The data illustrate the need to carefully consider the inner sphere (support) and outer sphere (anion) chemistry.